PERANCANGAN INTERIOR PET MEDICARE DI KOTA BLITAR - Irfa Kurnia; Ahmad Fajar Ariyanto (Pendhapa, 2018)
ABSTRACTEvery person has a tendency to love something and do a deep research into that activity. Daily routine drains energy of the people. That is why, hobby, such as taking care of pets become a refreshing activity that ‘recharge’ the energy that has been depleted. Pet hobby has become a trend and spreads to even remote areas, especially Blitar City. Communities such as Munchkin Minuet Cats, Brotherhood Gamedog (BROGAD), Kucing Addict, KDC and Canine were born in Blitar, but the facilities for fulfilling the needs of both pet dogs and cats are extremelyy limited. Only some pet food outlets and animal clinics which were not enough to complete the needs in one place (one stop service). That is why The Interior Design of Pet Medicare in Blitar City is going to answer that problem. Pet Medicare is there with many facilities that includes Medic, Care, Playspace, Meeting and Store that combine origami design theme with contemporary style. Origami that famous for its animal forms is packed with contemporary style which is so up-to-date and make it an interesting place for pet-lovers, veterinarians, and also animal owners.Keywords: Pet, Medicare, Blitar, Animal, Pets.